North and northerners: sociological surveys at the university - Victor R. Tsylev (Высшее образование в России)
This article outlines the specific features of the versatile activities of MSHU sociologicallaboratory. It emphasizes the many-sidedness of research work directions, determined by thelaboratory’s belonging to a higher education institution. The author mentions the laboratory’s advantages in studying the cultural and socio-economic situation in the region, determinedby the opportunity to involve in research the university teachers, specialized in problems under discussion.